The Analysis of Estella’s Characterization as The Main Character in “Cruella 2021” Movie - Risma Risma; Festi Himatu Karima; M. Wahyu Widiyanto (Institut Agama Islam Sunan Giri Ponorogo, 2022)
This research deals with characterization analysis. The objective of the research are (1) to know how Estella or Cruella’s characterization is described in “Cruella 2021” movie; (2) to know Estella or Cruella’s conflicts in “Cruella 2021” movie; 3) to know Estella or Cruella’s characterization can we emulate in “Cruella 2021” movie. The researcher used a qualitative approach based on a document study. The method used in this research is the descriptive method. The researcher took data from the script of the film “Cruella” as primary data. The researcher takes subtitles, several articles, and other secondary data sources related to the “Cruella” film. The researcher used the documentation technique to get the data in this research. The theory in this research combines structural approach and objective theory. The characterization analysis of this research is based on the characterization theory according to Jacob and Saini. The results and conclusion of this research are as follows; (1) Cruella’s characterization based on what the characters say, Cruella’s characterization are a good daughter, a good friend, a little psycho, a trouble maker, a grudge and brave. Based on what the characters do: grumpy, break promise, talented, trouble maker, grudge and a good friend. Based on what the others think/ say: talented, rude and evil ; (2) Cruella’s conflict; internal conflicts, Cruella blamed herself for her mother's death, so she was very sad, Cruella is furious knowing the real killer of her mother's death and that's what makes her want to take her revenge. External conflict, the conflict of Cruella with Baroness, the conflict between Cruella with her friends, Jasper and Horace (3) Cruella’s good characterization that can we emulate is a good daughter, a good friend, brave and talented.